Hematological parameters in endurance horses pre and post 120 km race (Revista de Ciências Agroveterinárias, 2023)
The endurance discipline has the shortest history in Bulgaria compared with other disciplines of equestrian sports. Endurance competitions are held over distances from 40 km to 160 km. The present study focused on the effect of exercise on horses over a distance of 120 km. Changes in the following hematological parameters were investigated: Leukocytes (WBC, g/l); Erythrocytes (RBC, T/l); Platelets (PLT, g/l); Hemoglobin (Hb, g/l); Hematocrit (HCT,%); Mean corpuscular volume (MCV, fl); Mean corpuscular hemoglobin (MCH, pg); Mean cell hemoglobin concentration (MCHC, g/l), Leukogram (Eos; Bas; Neu; Lym; Mon,%) as well as some electrolytes and hormone concentration. The study aimed to establish the changes in these indicators' values before and after the competition. Analysis of the haemogram showed a significant increase in the mean values ​​of 4 of the indicators under study. No significant differences were established in MCV, MCH and MCHC. A decrease was found in the number of Lym, Eos, and Mon and a significant increase in Neu after the competition. The concentration of electrolytes (Ca, Na and K) in the blood serum decreased, and the levels of CK and LDH significantly increased.
Keywords: electrolytes; hematology; horses; reference standards